Teacher training in Media Education: media use versus the development of critical and reflexive competencies - Tomé, V.; Helena Menezes (Advanced Educational Technologies - 6th WSEAS/IASME International Conference on Educational Technologies (EDUTE’10), 2010)
Initial and in service teacher training on Media Education is a key issue for its integration in the curricula. There are, however, different views about how it must be done. This paper presents one teacher training that is being delivered to 150 Portuguese teachers within the scope of a research project that follows the recommendations of the Second European Congress on Media Education, held in Italy in October 2009. It also presents the first results of the research project on media messages production by more than 600 students and 50 teachers in the 24 schools of Castelo Branco region.